Does new infrastructure improve public health? Evidence from smart city pilot program in China - Zhou, Sha; Ren, Jia (Frontiers in Public Health, 2025)
As a key pillar of new infrastructure development, smart city construction seeks to meet residents’ growing demand for high quality urban living by creating environments that are technologically integrated. To identify the causal effect of new infrastructure development on public health, we exploit the staggered launch of the national smart city pilot program in China as a quasi-natural experiment. We apply a multi-period difference-in-differences approach with 18,993 individual-level observations from 2010 to 2020. Our empirical results indicate that smart city construction significantly improves the health of residents, though the effect emerges with a time lag. The findings are consistently supported across robustness checks. Mechanism analysis reveals that smart city construction improves public health by raising income levels, increasing opportunities for physical exercise, and improving air quality. Further analysis shows that the health effects of smart city construction are heterogeneous across regions and city sizes. Theoretical implications and targeted policy recommendations are provided to promote public health in the context of smart city advancement.